Peningkatan Kompetensi Sosial Guru Melalui Workshop Guru di SDN-1 Sukajaya Tahun 2018 - Sawadi Sawadi (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
The professionalism of a teacher is a must in realizing knowledge-based schools, namely an understanding of learning, curriculum, and human development including learning styles (Kariman, 2002). In general, schools that have teachers with professional competence will apply